Wrogowie, historia pewnej milosci - Singer, Isaac Bashevis, 1904-1991; Batko, Zbigniew (Warszawa : MUZA SA, 2003)
Polish translation of "Sonim, geshikh te fun a libe" and the English "Enemies, a love story". A novel of a man who escapes the holocaust and settles in Brooklyn with his second wife. Trouble begins when his first wife appears, having escaped death in the holocaust.
Translation of: Enemies, a love story. originally published in the Jewish daily forward in 1966 under the title: Sonim, di Geshichte fun a Liebe.
Keywords: Holocaust survivors -- Fiction; Married people -- Fiction; Jews -- New York (State) -- New York -- Fiction; Jewish men -- New York (State) -- New York -- Fiction; New York (N.Y.) -- Fiction